Menuju Pelayanan Sosial yang Berkeadilan - Damanik, Janianton (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2011)
It is inevitable that the main weakness of social service management, whether committed by state or another actors, lies in the enforcement of justice. The root of the problem mainly lies on the social services approach which tends to be charitative and focuses more on image building. Charitative approach immediately raises the sense of unjust when the target group of clients are subordinate of service providers, while the image building motive tends to encourage the emergence of manipulative actions that offend the sense of justice. This paper offers an alternative idea of model in social services which is more equitable with emphasis on production process and mechanism, allocation and distribution of social resources to the public, as the essence of social services